Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12888-023-04567-5
|View full text |Cite
|
Sign up to set email alerts
|

Cultural determinants and resilience and recovery factors associated with trauma among Aboriginal help-seeking clients from an Aboriginal community-controlled counselling service

Abstract: In addition to resilience and resistance, collective and personal experiences of trauma are commonly cited within the context of Aboriginal and Torres Strait Islander and other Indigenous First People’s experiences of colonisation. This study investigated whether a range of risk and protective factors, including cultural determinants of social and emotional wellbeing, were associated with posttraumatic stress outcomes among 81 Aboriginal help-seeking clients from an Aboriginal community-controlled counselling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, a stepwise approach may be required beginning with cross-sectional studies investigating the relationships between adversity, strengths, and distress, as well as studies investigating whether the ARRQ is sensitive to change. These kinds of initiatives have progressed since development of the ARRQ, though further research is required [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a stepwise approach may be required beginning with cross-sectional studies investigating the relationships between adversity, strengths, and distress, as well as studies investigating whether the ARRQ is sensitive to change. These kinds of initiatives have progressed since development of the ARRQ, though further research is required [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the ACE studies that suggested a buffering role of positive affect, both studies on adult trauma found significant effects of positive affect-related moderators. In a sample of 81 Aboriginal Australian community adults attending a family counselling service, Gee et al 79 found a moderating effect of resilience resources encompassing both personal and relational/cultural strengths (and including a measure of positive affect). Those who had experienced more potentially traumatic events in their lifetimes reported higher levels of posttraumatic stress symptoms, but this association was not significant among those with high levels of strengths.…”
Section: Positive Affect As a Moderating Resilience Resourcementioning
confidence: 99%
“…78 Regarding PTEs in adulthood, positive affect may reduce the risks of posttraumatic stress and suicidality. 79,80 Similarly, in the context of stressful life events, positive affect may be protective against negative affect, depression, anxiety, and suicidal ideation. [81][82][83][84] Indeed, when depression itself is the stressor, positive affect may be protective against suicidality.…”
mentioning
confidence: 99%
“…Other instruments have moved toward the assessment of more general factors that promote or hinder mental health in a broader sense (e.g., emotional wellness and empowerment) rather than standard clinical measures (Haswell et al, 2010). Moreover, some scales for Indigenous groups have moved away from assessing negative constructs of mental illness, and toward strengths and resources associated with resilience, healing, and recovery (Gee et al, 2023).…”
Section: Holistic Constructs Of Mental Well-beingmentioning
confidence: 99%